2000
DOI: 10.1007/bf02345757
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mammalian skeletal muscle cells cultured on microcarrier beads in a rotating cell culture system

Abstract: The growth and repair of adult skeletal muscle are due in part to activation of muscle precursor cells, commonly known as satellite cells or myoblasts. These cells are responsive to a variety of environmental cues, including mechanical stimuli. The overall goal of the research is to examine the role of mechanical signalling mechanisms in muscle growth and plasticity through utilisation of cell culture systems where other potential signalling pathways (i.e. chemical and electrical stimuli) are controlled. To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…No mitotic cells were observed in either culture condition. Reduced proliferation has been previously noted in RCCScultured myoblast aggregates (Molnar et al 1997;Torgan et al 2000); however, these reports used support structures (beads, membranes) for cell growth. Interestingly, the appearance of visibly large cells was noted at the periphery of RCCS 6+ d aggregates (see Figs.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…No mitotic cells were observed in either culture condition. Reduced proliferation has been previously noted in RCCScultured myoblast aggregates (Molnar et al 1997;Torgan et al 2000); however, these reports used support structures (beads, membranes) for cell growth. Interestingly, the appearance of visibly large cells was noted at the periphery of RCCS 6+ d aggregates (see Figs.…”
Section: Resultsmentioning
confidence: 92%
“…These have included collagen lattice (Cheema et al 2003), collagencoated microcarrier beads (Molnar et al 1997;Torgan et al 2000), and fibrin gel (Huang et al 2005). The use of preexisting extracellular matrix (ECM) can stimulate endogenous myotube ECM production (Vandenburgh et al 1974).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following these findings, we hypothesized that IR laser radiation could be a useful tool to counteract the microgravity-induced impairment of energetic metabolism , cytoarchitectural alterations (Pache et al 2010) and decrease in the levels of contractile proteins (Torgan et al 2000) observed in myoblasts exposed to microgravity.…”
Section: Introductionmentioning
confidence: 99%
“…The C2C12 cells are widely accepted as a model to study the behaviour of satellite cells (Burattini et al 2004), which play a crucial role in skeletal muscle regeneration and repair (Wang and Rudnicki 2012) and are capable to repopulate atrophied muscle (Hawke and Garry 2001). Moreover, C2C12 cells have been already used in previous studies regarding the effects of microgravity on mechanical signalling mechanisms in muscle plasticity (Torgan et al 2000) and myoblast behaviour (Slentz et al 2001;Pache et al 2010).…”
Section: Introductionmentioning
confidence: 99%